Redressing Canada's Second World War Narrative. (2nd July 2020) - Cook, Tim
Abstract : In early 1942, 23, 000 Japanese Canadians on the West Coast were forcibly relocated against their will to the interior of Canada after Japan entered the war against the Allies. This forced relocation left deep scars in that community. Decades later, Japanese Canadians mounted a redress campaign for an official apology and financial restitution. This provocation examines that campaign and explores how it has shaped Canada's constructed memory of the Second World War.